Big-Five Personality Traits Mapped with Software Development Tasks to Find Most Productive Software Development Teams - Iqbal, M. Aqeel; Aldaihani, Adel Rashed; Shah, Asadullah (International journal of innovative technology and exploring engineering, 2019)
The software development lifecycle defines a systematic way of developing good quality software to meet customer expectations about scope, time and budget. Each phase of this development lifecycle is distinct and rigorous which defines an independent body-of-knowledge within the domain of software engineering. Consequently, each phase of development lifecycle demands a different set of skills and personality traits for software engineers to cope-up their work effectiveness to improve the software development process. Hence, it is obligatory to highlight the most relevant personality traits of software engineers working for different phases of development lifecycle. In this regard, this article presents a comprehensive study in which the most relevant personality traits of software engineers have been highlighted for different tasks/phases of software development lifecycle. The big-five personality model has been used to evaluate and correlate the personality of software engineers for each phase due to its wide acceptance in the research and development community.